REGENERASI TANAMAN ANGGREK MERPATI (Dendrobium crumenatum Swartz) PADA MEDIA KULTUR DENGAN TAMBAHAN ZEATIN DAN SUKROSA - Khusnul Nur Azizah; Fathurrahman; Hasan Basri Jumin (Ekoagrotrop, 2023)
The need for orchids is increasing and the orchids are threatened with extinction due to forest exploitation and need to be supported by the provision of seeds using tissue culture technology. The research entitled regeneration of the pigeon orchid (Dendrobium crumenatum Swartz) aim of this study was to determine the effect of the interaction between the concentrations of growth regulators zeatin and sucrose on the growth of Dendrobium crumenatum Swartz callus in vitro. The experimental design used was a factorial randomized block design consisting of 2 factors. The first factor is the zeatin dose consisting of without treatment, 0.1, 1.0, and 10 ppm. The second factor is the sucrose dose consisting without treatment, 20, 40, and 60 g/l, there are 16 treatment combinations and 3 repetitions so that 48 experimental units were obtained. Each experimental unit consisted of 4 explants, so that a total of 192 explants were explants. The parameters observed were as follows: percentage of live explants, percentage of rooted explants, percentage of explants that formed callus, number of shoots, number of leaves, and chlorophyll content Follow-up test Honest Significant Difference (HSD) at 5% level. The interaction of zeatin and sucrose affects the survival percentage of explants and callus, the number of shoots and the number of leaves. The best treatment was 1.0 ppm zeatin and 40 g/l sucrose. The main effect of the best zeatin concentration is 1.0 ppm and the best dose concentration is sucrose 40 g/l.